A HERMENEUTIC INTERPRETATION OF NAHEED QAMAR’S POEM “HUM PARINDAY KOI” (Al-Aasar, 2025)
This research intends to explore the underlying themes of Naheed Qamar’s Urdu poem “Hum Parinday Koi” (We are Birds) through the lens of literary hermeneutics. Drawing on linguistic, historical, and holistic analysis, the study seeks to uncover how the poem reflects the shaping of identities across history, evolution, and time. Qamar employs seven powerful metaphors birds, stars, stones, trees, travelers, oceans, and toys to capture the complexities of human existence. The poem suggests that time itself carries the dual force of joy and sorrow, continuously molding the experiences of human communities. At the same time, it introduces a mysterious, unseen presence that records and witnesses the destiny of humankind, reminding us of the fragile, yet profound, relationship between history, identity, and fate.